Kajian Pemanfaatan Debit pada Saluran Irigasi untuk Pembangkit Listrik Tenaga Mikrohidro (Studi Kasus Saluran Induk Sawito Daerah Irigasi Sadang) Kabupaten Pinrang, Propinsi Sulawesi Selatan - Ghofar, Abdul; Sunarto, Bambang; Sembiring, Kristina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Utilization of water as a new power plant reaches about 6.9% of the existing potential and most of it is built in rivers with very large costs and quite a long time. The demand for electricity is increasing more and more, but the government cannot add power plants from fossil fuels. In fact, they will gradually close all of them and replace them with new renewable energy plants, such as hydropower, solar power, PLTB and other renewable energy power plants. In general, hydroelectric power plants (PLTA) are built on river bodies in the form of weirs or weirs so that they require considerable cost, time and risk and are greatly influenced by fluctuations in discharge, sediment and so on. While there are many irrigation areas that have operated with discharge capacity and fall height that can be utilized for small-scale hydropower, one of them is the Sadang Irrigation Area with an area of Â±64,000ha. Using topographic mapping methods, measuring surveys of existing channels, and analyzing the availability of discharge and irrigation water requirements, the research results showed that the height of falls in several irrigation buildings was obtained. By analyzing water availability and demand (water balance), a water supply plan for each existing irrigation canal is obtained. so that the potential power and electrical energy produced is obtained. The Sadang irrigation area is supplied with water from the Benteng weir through two intake buildings. The right intake building supplies the Pekkabata main channel, while the Sawito and Rappang Ha main channels are supplied from the left intake building. The Pekkabata sub-network has a potential power of 338 kW, the Rappang sub-network has a potential power of 158 kW and the Sawito sub-network has a power of 1,939 kW. So the total potential electrical power in the Sadang irrigation network is 2,436 Kw. The potential that has been developed in the Sadang irrigation area for electricity generation is 1,235 kW so there is still a potential of 1,200 kW. Especially in the Sawito main channel, in the building for tapping BSa. 9 has an electrical potential with a power of 492 kW, and annual energy production of 3,511,880 kWh, and the suitable turbine type is the kaplan type.